1979
DOI: 10.1159/000194097
|View full text |Cite
|
Sign up to set email alerts
|

Phlebotomy improves Pulmonary Gas Exchange in Chronic Mountain Polycythemia

Abstract: There is not unanimous agreement in the literature regarding the effects of bleeding on pulmonary gas exchange in polycythemic patients. Spirometry, alveolar-arterial O2 and CO2 tension differences, PaO2 breathing 100% oxygen and carbon monoxide-diffusing capacity were measured before and after 1 week of chronic phlebotomy in 4 chronic mountain polycythemic patients. Studies were carried out at 3,700 m above sea level (PB = 491 mm Hg). Before phlebotomy, 2 patients s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

1984
1984
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 22 publications
(43 reference statements)
0
17
0
Order By: Relevance
“…Previous human studies have also suggested that an excessive increase in blood viscosity is involved in impaired gas exchange and reduced exercise performance. This has been observed in cases of polycythemia vera (27), high-altitude polycythemia, and chronic mountain sickness (4,52,53). Of note, upon either phlebotomy or hemodilution that reduced the hematocrit from excessive to normal (e.g., sea level) values, individuals experienced a stimulation of ventilation and an improved ventilation-perfusion pattern.…”
Section: Discussionmentioning
confidence: 90%
“…Previous human studies have also suggested that an excessive increase in blood viscosity is involved in impaired gas exchange and reduced exercise performance. This has been observed in cases of polycythemia vera (27), high-altitude polycythemia, and chronic mountain sickness (4,52,53). Of note, upon either phlebotomy or hemodilution that reduced the hematocrit from excessive to normal (e.g., sea level) values, individuals experienced a stimulation of ventilation and an improved ventilation-perfusion pattern.…”
Section: Discussionmentioning
confidence: 90%
“…Treatment for CMS includes relocation to a lower altitude, periodic phlebotomy [84], isovolemic hemodilution [85,86] or supplemental oxygen [87]. The long-term use of respiratory stimulants, such as medroxyprogesterone [88] or acetazolamide [89-91], also improves oxygenation and polycythemia in CMS patients.…”
Section: Respiratory Disorders Associated With Chronic Exposure To Himentioning
confidence: 99%
“…MONGE and WHITTEMBURY [56] described a syndrome marked by the triad of polycythaemia, hypoxaemia and impaired mental function in which affected individuals complain of headache, fatigue, impaired concentration, irritability and impaired exercise tolerance, and physical examination demonstrates clubbing, congested mucosal surfaces and cyanosis. Treatment involves relocation to lower elevations or, in cases where relocation is not feasible, periodic phlebotomy [57], isovolaemic haemodilution [58,59] and long-term use of respiratory stimulants such as acetazolamide [60] or medroxyprogesterone [61]. Right heart failure was not described in the report by MONGE and WHITTEMBURY [56], but has subsequently been described in advanced stages of the disease in populations outside the Andes [62].…”
Section: High-altitude Illnessmentioning
confidence: 99%